PENDEKATAN METODE FULL COSTING DALAM PENENTUAN HARGA POKOK PRODUKSI PADA USAHA PISANG SALE - Dara Utamie; Baiq Qistinnisa (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2025)
This study explores the implementation of the Cost of Goods Sold (COGS) calculation method using the full costing approach at UD Affan, a banana fritter producer in West Lombok. Using a descriptive qualitative approach, data collection was conducted through observation, interviews, and document collection. The findings indicate that UD Affan has not yet adopted adequate accounting practices, resulting in fixed costs not being included in the COGS calculation. With the full costing approach, COGS is recorded at Rp 10,223 per pack, which is higher than the current selling price of Rp 10,000. This condition results in losses and indicates the importance of regular cost recording. This study recommends consistent cost recording and adjusting selling prices to ensure business continuity. Keywords: Cost of Goods Sold, Full Costing, Banana Sale